All inorganic coordination polymers have been made possible with the m-carboranylphosphinate ligand. Issue 41 (8th October 2018) - Oleshkevich, Elena; Romero, Isabel; Teixidor, Francesc; Viñas, Clara
Abstract : All inorganic coordination polymers (CPs) of Mn II, Cd II and Zn II have been achieved by using purely inorganic m -carboranylphosphinate ligands as a versatile building block bridging each of the two metal centres. The first described Cd II polymer with phosphinate ligands is reported in this work. Abstract : New examples of 1D coordination polymers (CPs) and complexes containing the purely inorganic carboranylphosphinate ligand [1-OPH(O)-1, 7- closo -C2 B10 H11 ] − are reported. The reaction of Na[1-OPH(O)-1, 7- closo -C2 B10 H11 ] salt with MCl2 (M = Mn, Co, Ni, Cu, Zn and Cd) in MeOH or EtOH leads to compounds1–8 . All compounds have been exhaustively characterized by analytical and spectroscopic techniques. X-ray analysis and spectroscopy characterization revealed the differences between the isolated compounds: 1D polymeric chains (CPs) with carboranylphosphinate ligand bridges have been obtained with Mn II, Cd II or Zn II centres, whereas compounds with low nuclearity have been isolated with Cu II, Co II and Ni II . No polymeric structures were obtained in the Co II and Ni II complexes due to the higher affinity of these metals for water than that for the m -carboranylphosphinate and accordingly, these complexes generate supramolecular hydrophobic/hydrophilic structures. The reactivity of manganese polymer1 with water leads to the breakage of the polymer with the formation of a new mononuclear compound2, and that in methanol leads back to the initial polymer1 . However, the reactivity of polymer1 with 2, 2′-bpy maintains the core present in the initial polymer, leading to the CP3, which in methanol/water medium produces species of lower nuclearity. The magnetic properties of the compounds studied show weak antiferromagnetic coupling.